2016
DOI: 10.4034/pboci.2016.161.43
|View full text |Cite
|
Sign up to set email alerts
|

Dental Environment Stress: Findings among Lusophone Dental Students

Abstract: Objective: To perform cross-cultural adaptation of the Dental Environment Stress (DES), to test its construct validity and reliability, and to identify the sources of stress among Brazilian dental students. Material and Methods: The DES was transculturally adapted to Portuguese using translation/back-translation, review by an expert bilingual committee and consensus building. The first version was tested in a sample of 42 dental students to check the understanding level of the alternatives. The final version w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 23 publications
3
13
1
1
Order By: Relevance
“…Longitudinal observations proved that stress related to work overload and clinical factors increased along with the duration of studies, while those associated with faculty and administration factors decreased. This contradicts the research by Menck Sangiorgio et al [24] which indicated a decrease in the overall levels of stressors as students progressed with their program. However, it should be remembered that the results presented here refer to the situation at a specific university.…”
Section: Comparison Of Students Of Different Years Of Studies In Termcontrasting
confidence: 67%
See 3 more Smart Citations
“…Longitudinal observations proved that stress related to work overload and clinical factors increased along with the duration of studies, while those associated with faculty and administration factors decreased. This contradicts the research by Menck Sangiorgio et al [24] which indicated a decrease in the overall levels of stressors as students progressed with their program. However, it should be remembered that the results presented here refer to the situation at a specific university.…”
Section: Comparison Of Students Of Different Years Of Studies In Termcontrasting
confidence: 67%
“…As in other studies, the lowest level of stress was noted in the domains of personal factors and living accommodation [19,20,23,24]. In the latter area, the greatest stressor was the lack of time for rest/relaxation, especially in the fourth and fifth years of studies.…”
Section: Comparison Of Students Of Different Years Of Studies In Termsupporting
confidence: 66%
See 2 more Smart Citations
“…In our study, female students had higher levels of stress than male counterparts in all stress domains except for "social stressors" domain. Many studies reported gender-related differences regarding DES (17,20,(37)(38)(39). Female students were more open to express stress issues than their male counterparts, and their response to stressors also differed.…”
Section: Discussionmentioning
confidence: 99%